Differences in biathlon standing shooting performance in senior and junior biathletes - Köykkä, M.; Ihalainen, S.; Laaksonen, M. S.; Häkkinen, K. (19th International Symposium "Modern Science and Practice for Strength and Endurance Training" October 10-12, 2018, 2018)
Compared to junior biathletes, national team biathletes have demonstrated higher hit percentage in rest and better front leg balance in race simulated shooting[1]. The present study investigated differences between age groups. 13 senior (>20 years old) and 10 junior (16-20 years old) biathletes fired 8x5 standing shots at rest (REST) and 2x5 shots during a race simulation of 2x5 min at 95% of maximal heart rate (RACE). Mean values in both conditions were calculated for shooting performance (hit%), horizontal and vertical (DevY) stability of hold (standard deviation of the aiming point 0-0.6 s before the shot), aiming accuracy, cleanness of triggering (ATV, distance travelled by the aiming point 0-0.2 s before the shot), postural balance (standard deviation of the center of pressure location 0-0.6 s before the shot) of the whole body in shooting (SDY) and cross-shooting (SDX) direction, and postural balance of each leg separately (SD*_F, front; SD*_R, rear). In REST, senior biathletes demonstrated better hit% (92 ± 6% vs 82 ± 8%, p<0.01), DevY (16 ± 5 mm vs 23 ± 6 mm, p<0.01), ATV (51 ± 7 mm vs 60 ± 10 mm, p<0.05) and SDY (0.62 ± 0.15 mm vs 0.78 ± 0.17 mm, p<0.05), thus indicating better shooting technical abilities. In RACE, only DevY (20 ± 5 mm vs 28 ± 8 mm, p<0.01) and SDY_R (0.25 ± 0.06 mm vs 0.36 ± 0.10 mm, p<0.05) were better in seniors, indicating that they could not maintain their better abilities, and should focus on race shooting routines. SDX, SDY, SDX_F, SDX_R and SDY_R decreased significantly in juniors (all p<0.05), whereas only SDY and SDY_R decreased in seniors (both p<0.05), indicating that race simulation deteriorated postural balance more in juniors, who should therefore focus on training specific balance under fatigue conditions too.